Microbiological Indication of Soils in Zone of Influence of Perechin Timber and Chemical Plant - Kryvtsova, Maryna; Bobrik, Nadija; Sabov, Marjan; Sabov, Mark (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The soil is the most sensitive indicator of the environmental and geochemical state of the ecosystems, for it is there that all migration ways of chemical elements, including toxic ones, intersect. It is important to consider the reaction and role of soil microbial associations that on the one hand sensitively react to a technogeneous impact and on the other hand take part in soil formation processes and determine to a considerable extent the plants’ soil growth conditions. The purpose of the paper is to study the factory impact (Perechin timber and chemical plant) upon the soil microbiota, to identify the level of heavy metals and nitrates in the soil covered with lawn herbage, and to evaluate the air pollution by microbiological indicators. A complex study of the state of the microbiota, contents of heavy metals and nitrates in the soils near the factory is conducted. The soils located in the factory influence’s zone are shown to be characterized by a heightened content of Pb and Zn as compared with the maximum permissible concentrations (MPC) for these metals. Excess of the background values of the heavy metals under review proved presence of a significant technogeneous pollution. The study recorded the reconstruction of the microbial soil coenosis as compared with the control. The soil microbiocoenosis is established to have undergone a reconstruction characterized by an increased number of oligotrophs, ammonifiers and a decreased content of Azotobacter. It has been ascertained that the highest level of nitrates was recorded in the soil of Spot 30 m from factory.